RGB colour image watermarking using canny edge detection and Discrete Wavelet Transform (DWT) [electronic resource] - Sia, Hwee Boon, 1989- (2013)
Project Paper (Sarjana Muda Sains Komputer (Perisian Grafik dan Multimedia)) - Universiti Teknologi Malaysia, 2013